DESIGN OF A PRELOVED MARKETPLACE WEBSITE APPLICATION FOR UNIVERSITY STUDENTS - Alfi Mahgfiro; Avissya Febrian; Riski Tri Maulana; Nurlaila Syafitri; M. Reddy Syahputra; Frimus Susanto Elianda; Miftahul Jannah (Ninety Media Publisher, 2026)
The rapid development of information and communication technology has significantly influenced commercial activities, including buying and selling transactions conducted through digital platforms. Among university students, the increasing demand for affordable products has encouraged the growth of preloved or second-hand goods trading. However, existing general marketplace platforms do not specifically accommodate the needs of university students in conducting preloved transactions within campus environments, resulting in inefficiencies in product searching, limited transaction relevance, and concerns regarding security and trust. This study aims to design a website-based Preloved Marketplace application specifically intended for university students to facilitate secure, efficient, and affordable buying and selling activities for second-hand usable goods. The research employed a qualitative approach through observation, interviews, surveys, literature review, and system requirement analysis. The design process included problem identification, UI/UX design using Figma, prototype implementation, and system evaluation. The developed application provides various features, including user registration, login, product listings, product search and filtering, shopping cart, checkout, payment confirmation, live chat, sales reports, and dashboard monitoring. Black Box Testing was conducted to evaluate system functionality based on user input and output behavior. The testing results indicate that all system features operated successfully according to expected requirements, demonstrating functional consistency and usability. The developed platform is expected to support university students in selling unused but still usable products while helping other students obtain affordable necessities. Therefore, the proposed Preloved Marketplace has strong potential to improve transaction efficiency, support sustainable consumption, and encourage digital transformation within campus communities.